SAT0179 Efficacy and Safety of Rituximab in Patients with SLE And Systemic Vasculitides. (23rd January 2014) - Moiseev, S.; Novikov, P.; Meshkov, A.; Kuznetsova, E.; Zhabina, E.; Lopatina, I.; Bulanov, N.
Abstract : Background: Biologic agents are established treatment for rheumatoid arthritis while their efficacy in patients with systemic lupus erythematosus (SLE) and systemic vasculitides requires confirmation in additional studies. Objectives: To evaluate the efficacy and safety of rituximab in patients with SLE and systemic vasculitides. Methods: We enrolled in open-label uncontrolled trial all consecutive patients with severe SLE and systemic vasculitides that were treated with rituximab. Efficacy and safety of treatment was evaluated at 6 months using clinical and standard immunological criteria (eg. ANCA, ds-DNA, CRP) and specific scales (BVAS, SLEDAI):complete remission – resolution of activity and tapering of steroids, incomplete remission – significant improvement of signs and symptoms. Results: During 3 years 57 patients were enrolled in 6-month trial: ANCA-associated vasculitides – 27 (granulomatosis with polyangitis [Wegener's] – 24, microscopic polyangitis – 2, Churg-Strauss syndrome – 1), SLE – 16, cryoglobulinemic vasculitis – 11, urticarial vasculitis – 1, Takayasu arteriitis – 1, giant cell arteritis – 1. All patients had severe visceral disease that was refractory to standard treatment including high dose cyclophosphamide and steroids. BVAS and SLEDAI scores averaged 16.8 and 11.2 points, respectively. The vast majority of patients responded to rituximab administration (500 mg weekly, 4 infusions). At 6 months complete and incomplete remission was achieved respectively in 17 (63.0%) and 9 (33.3%) patients with ANCA-associated vasculitides, 9 (56.3%) and 7 (43.7%) patients with SLE, 6 (54.5%) and 5 (45.5%) patients with cryoglobulinemic vasculitis, all patients with other vasculitides. In total 56 (98.2%) patients responded to rituximab at 6 months (complete remision in 59.6% of patients and incomplete remision in 38.6% of patietns). Average BVAS and SLEDAI scores have reduced to 1.6 and 3.2 points, respectively. The safety of rituximab was acceptable for patients with severe autoimmune disease who continued immunosuppresive treatment after biologic agent administration. Majority of adverse events were mild or moderately severe and did not require discontinuation of treatment. Serious adverse events were reported in 4 (7%) patients and included late neutropenia (in 2), severe infusion reaction (in 1) and death due to Nocardia sepsis (in 1). Conclusions: Rituximab has favorable risk/benefit ratio in selected patients with severe SLE and ANCA-associated and crioglobulinemic vasculitides. Its efficacy in patients with other forms of vasculitides should be additionally studied. Disclosure of Interest: None Declared